1995
DOI: 10.1002/mrd.1080410408
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the intermediate filament proteins vimentin, keratin, and desmin in the bovine ovary

Abstract: The distribution of the intermediate filament (IF) proteins desmin, keratin, and vimentin was studied immunohistochemically in bovine ovaries. Special attention was paid to granulosa cells to examine possible marked changes of IF distribution in relation to folliculogenesis during ovarian development. Therefore, ovaries were used from fetuses from 3 months of gestation onward, calves, heifers, and cows. In all ovaries, desmin immunoreactivity was restricted to smooth muscle cells in blood vessel walls. Keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
6
24
0
Order By: Relevance
“…Previous studies have demonstrated that changes and destabilization of the cytoskeletal proteins (microtubules, microfilaments and intermediate filaments) of the ovary decrease hardly the production of steroid hormones and can contribute with the cystogenesis (Chen et al 1994). Although the expression of cytoskeletal proteins has been studied in normal ovarian structures of many species including the sheep (Marettova & Maretta 2002), cow (Van der Huck et al 1995) and rat (Selstam et al 1993), there are no investigations about the expression of these proteins in normal and affected swine ovary. Recently, it was suggested that cytoskeletal proteins conducting the functional and structural changes during the cystogenesis participated in the pathogenesis of the COD in rats ) and in cows (Ortega et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that changes and destabilization of the cytoskeletal proteins (microtubules, microfilaments and intermediate filaments) of the ovary decrease hardly the production of steroid hormones and can contribute with the cystogenesis (Chen et al 1994). Although the expression of cytoskeletal proteins has been studied in normal ovarian structures of many species including the sheep (Marettova & Maretta 2002), cow (Van der Huck et al 1995) and rat (Selstam et al 1993), there are no investigations about the expression of these proteins in normal and affected swine ovary. Recently, it was suggested that cytoskeletal proteins conducting the functional and structural changes during the cystogenesis participated in the pathogenesis of the COD in rats ) and in cows (Ortega et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…In older investigations of human [Czernobilsky et al, 1985] and other mammalian ovaries [van den Hurk et al, 1995], co-expression of vimentin and CK filaments was demonstrated at the granulosa layer. In the rat, as the follicular epithelium becomes multi-layered during follicular growth, keratin was retained by granulosa cells adjacent to the follicular basement membranes but disappeared from cells that were displaced towards follicle centres.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these studies, vimentin and CKs were detected within the granulosa cells of follicles at various stages of growth and atresia, in luteal cells of the corpus luteum throughout the luteal phase, and in oocytes from both fetal and adult ovaries [Czernobilsky et al, 1985;Gall, 1991;Santini et al, 1993;Gallicano et al, 1994;van den Hurk et al, 1995;Marettová and Maretta, 2002]. Of vertebrate germ cells, nuclear IFs, called lamins, have thus far only been found in the oocytes of Xenopus [Gall et al, 1989] and in the oocytes of mice [Arnault et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tubules are usually located in the hilus of the ovary, but may extend through the medulla or be isolated in the mesovarium adjacent to the hilus 1 . Rete epithelium is immunoreactive for cytokeratins, desmoplakins and vimentin, and has numerous desmosome-tonofilament complexes as seen by electron microscopical examination 2,3 . O'Shea observed mucinous secretion of non-sulfated, acid mucopoly-saccharide in the rete tubules of dogs 4 .…”
mentioning
confidence: 99%